Determination of Groundwater Flow near a Borehole Heat Exchanger using the Temperature Sensor Module (TMS; 82m; outer rings) - Alexander Michalski; Norbert Klitzsch (PANGAEA, 2019)
Here, we present the first application of the temperature sensor module (TSM) for detecting groundwater flow velocity and direction. The TSM maps the horizontal temperature distribution around a borehole heat exchanger (BHE). Groundwater flow distorts this temperature distribution. Thus, flow velocity and direction can be inferred from the measured temperatures. As modular systems, TSMs can be attached to BHE at any depth of interest. For the studied BHE, the depths of interest are at 82 m and 94 m, where we installed TSMs. We recorded TSM data for two weeks before and during the operation of the BHE. After simulating the working fluid temperature in the depths of interest, we model the horizontal temperature distributions using the working fluid temperatures as input. By minimizing the root mean square error between the measured and simulated temperatures, we obtain groundwater flow of (0.4 ± 0.1) m per day in NW direction in 82 m depth and no-flow or flow below the detection limit (0.01 m to 0.02 m per day according to the temperature difference between inlet tubes and outlet tubes ) in 94 m depth, respectively. The results agree within the error bounds with the groundwater flow obtained by an optical method.
In supplement to: Michalski, A; Klitzsch, N (2019): First field application of temperature sensor modules for groundwater flow detection near borehole heat exchanger. Geothermal Energy, 7(1), https://doi.org/10.1186/s40517-019-0152-5